Identifying Improvement Opportunities in Software Engineering Education at the Maranhão State: Listening to Voices from Academy and Industry - Costa, Yandson; Gomes, Dayanne; Santos, Sebastião; Pinto, Nathasha; Viana, Davi; Braz, Geraldo; Rivero, Luís (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
The teaching of Software Engineering (SE) has become challenging due to the large amount of content taught and the constant evolution of the software industry, directly impacting the requirements necessary to apply for a position in the area of Information Technology (IT). In this context, it is clear that students of computer courses still find it difficult to know how to prepare for the job market, and Higher Education Institutions (HEIs) may have difficulties in aligning themselves with market expectations with their syllabus in SE. This paper aims to provide a holistic view of the teaching-learning process, involving the views of students, HEIs and IT companies in the context of the state of Maranhão; and to propose reflections on the current state of the education to complement the contents and methodologies applied in the classroom with the needs of the local industry. To do so, three activities were carried out: (1) mapping expectations and evaluating higher education from the students' point of view; (2) analysis of higher education disciplines in higher education institutions in the state of Maranhão in Brazil; and (3) survey of expectations of the IT market considering the vacancies disclosed in relation to the SE area in the state of Maranhão. The results indicate a partial fulfillment of the demand regarding the taught topics related to SE from the local industry by the HEIs. In addition, there is a need to improve the teaching-learning methodological processes, focusing on practical activities and the learning of teamwork skills, in addition to knowledge in software development.